Nutritional and Psychosocial Considerations in Head and Neck Cancer Survivorship: An Integrative Narrative Review - Asiri, Fatimah Hadi Ahmed; Maha Rashed Alqahtani; Bayan Nawaf Alshammari; Ali Ahmed Khadhi; Khalid Fahad Alharbi; Zamzam Nawaf Alshammari; Basmah Adel S Alsoudmi; Nawaf Monahi D Alotaibi; Maher Sajdi Mashal Alotaibi; Obaid Salman Tamim Aldossary (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Head and neck cancer (HNC) survivorship presents complex challenges that extend beyond tumor eradication, profoundly impacting nutritional status, psychological wellbeing, and social functioning. The multimodal treatments often cause lasting sequelae including dysphagia, xerostomia, and tissue damage, requiring coordinated interdisciplinary management. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes evidence on the integrated management of HNC survivors, focusing on the intersection of oncology nursing, dental care, clinical nutrition, psychosocial support, and laboratory monitoring. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature search was conducted across PubMed, CINAHL, Scopus, and PsycINFO databases (2013-2025) using keywords related to HNC survivorship, nutrition, psychosocial care, and interdisciplinary management. The review included clinical trials, observational studies, systematic reviews, and clinical guidelines. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence demonstrates that integrated care models significantly improve outcomes across domains. Proactive dental interventions reduce osteoradionecrosis risk by 60%, while specialized dysphagia management decreases aspiration pneumonia incidence. Psychosocial interventions address the 30-40% depression prevalence among survivors, and systematic nutritional support prevents severe weight loss. Regular laboratory monitoring enables early detection of endocrine dysfunction and nutritional deficiencies. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> HNC survivorship requires an integrated, proactive approach addressing the interconnected physical, nutritional, and psychosocial sequelae. Future care models should prioritize standardized interdisciplinary protocols that bridge specialty divides to optimize quality of life for this vulnerable population.